THE ROLE OF DISCOURSE MARKERS AS INDICATORS OF SOCIAL RELATIONS IN ENGLISH AND UZBEK FICTION - Qo’chqarova Yoqutxon (TADQIQOTLAR, 2025)
Abstract:This article examines the sociopragmatic role of discourse markers as indicators of social relations in English and Uzbek fictional discourse. Discourse markers, including pragmatic particles, connectives, fillers, and formulaic expressions, function as essential tools for organizing discourse, managing interaction, and signaling interpersonal relationships between characters. The study adopts a comparative qualitative approach to analyze how discourse markers reflect power relations, social distance, politeness, solidarity, and cultural norms within literary communication. The findings reveal that English fiction tends to employ discourse markers to express individual stance, indirectness, and conversational mitigation, whereas Uzbek fiction relies more heavily on culturally embedded markers that encode respect, hierarchy, and collective identity. The article demonstrates that discourse markers are not peripheral linguistic elements but key sociopragmatic resources contributing to character development, narrative coherence, and cultural representation in literary texts.